Lactobacillus rhamnosus GG ameliorates noise-induced cognitive deficits and systemic inflammation in rats by modulating the gut-brain axis - Li, Xiaofang; Zheng, Pengfang; Cao, Wa; Cao, Yang; She, Xiaojun; Yang, Honglian; Ma, Kefeng; Wu, Fangshan; Gao, Xiujie; Fu, Yu; Yin, Jiayi; Wei, Fei; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Environmental noise exposure is linked to neuroinflammation and imbalance of the gut microbiota. Promoting gut microbiota homeostasis may be a key factor in relieving the deleterious non-auditory effects of noise. This study aimed to investigate the effect of Lactobacillus rhamnosus GG (LGG) intervention on noise-induced cognitive deficits and systemic inflammation in rats. Methods Learning and memory were assessed using the Morris water maze, while 16S rRNA sequencing and gas chromatography-mass spectrometry were used to analyze the gut microbiota and short-chain fatty acid (SCFA) content. Endothelial tight junction proteins and serum inflammatory mediators were assessed to explore the underlying pathological mechanisms. Results The results indicated that Lactobacillus rhamnosus GG intervention ameliorated noise-induced memory deterioration, promoted the proliferation of beneficial bacteria, inhibited the growth of harmful bacteria, improved dysregulation of SCFA-producing bacteria, and regulated SCFA levels. Mechanistically, noise exposure led to a decrease in tight junction proteins in the gut and hippocampus and an increase in serum inflammatory mediators, which were significantly alleviated by Lactobacillus rhamnosus GG intervention. Conclusion Taken together, Lactobacillus rhamnosus GG intervention reduced gut bacterial translocation, restored gut and blood-brain barrier functions, and improved gut bacterial balance in rats exposed to chronic noise, thereby protecting against cognitive deficits and systemic inflammation by modulating the gut-brain axis.